Caspase-3 mediated Apoptosis AT the endometrial hyperplasia in women of reproductive age - V. G. Dubinina; O. M. Nosenko; K. P. Vizir; O. A. Kaushik (Kazimierz Wielki University, 2016)
Dubinina V. G., Nosenko O. M., Vizir K. P., Kaushik O. A. Caspase-3 mediated Apoptosis AT the endometrial hyperplasia in women of reproductive age. Journal of Education, Health and Sport. 2016;6(12):883-894. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.255683 http://ojs.ukw.edu.pl/index.php/johs/article/view/4188         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.12.2016. Revised 20.12.2016. Accepted: 25.12.2016.   caspase-3 mediated Apoptosis AT the endometrial hyperplasia in women of reproductive age   V.G. Dubinina1, O. M. Nosenko1, K. P. Vizir1, O. A. Kaushik2   1odessa national Medical university, office@odmu.edu.ua 2pathomorphological laboratory «СSD Health Care», Kiev, csd@csdclinic.com.ua   Summary The study of apoptosis in hyperplastic endometrium of reproductive age women has been conducted. Caspase-3 expression in proliferative phase of the menstrual cycle was measured. 120 women of reproductive age of the main group with histologically confirmed diagnosis of nonatypical endometrial hyperplasia and 30 conditionally healthy gynecological patients of the control group were examined. All patients of the main group underwent hysteroscopy with separate scraping the uterine cavity, and the control group patients - endometrial paypel-biopsy. Apoptotic cells in the glands of the endometrium in women in the control group were recorded at 2.88 times (p<0,01) more often than in the stroma. Immunostaining of epithelial cells to caspase-3 inpatients with endometrial hyperplasia glands was larger than that in the stroma to 3.53 times (p <0,01). But at the same time, it revealed a decrease in the number of irregular immunostaining of apoptotic cells in the endometrial hyperplasia compared with the control in the stroma in 1.83 times (p <0,01) and in the glands - in 1,49 (p <0,01). Thus, in the presence of the hyperplastic endometrium in patients of reproductive age it was observed uneven intensity reduction of apoptosis in the cells of the endometrial glands and stroma, more pronounced in the stromal compartment. Key words: reproductive years, endometrial hyperplasia, apoptosis, stroma, glands, caspase-3.